2016
DOI: 10.1177/1541204016680403
|View full text |Cite
|
Sign up to set email alerts
|

School Strictness and Disproportionate Minority Contact

Abstract: There are racial and ethnic disparities associated with school discipline practices and juvenile justice contact. In addition, research suggests that stricter school discipline practices and disproportionate minority contact for minority youth are relatively more prevalent in urban areas. What remains unknown, however, is the relationship between race and ethnicity, school discipline practices, and juvenile justice referrals across urban, rural, and suburban schools. Therefore, this study draws from the Texas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 44 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Black and Native American youth in particular are also more likely than their White peers to be identified to receive special education services for emotional disturbance (Bal et al, 2019; Donovan & Cross, 2002) and placed in more restrictive special education settings (Skiba et al, 2006). Exclusionary discipline and restrictive special education placements is associated with decreased academic achievement (Morris & Perry, 2016) and rates of school completion (Marchbanks & Blake, 2018; Oelrich, 2012), as well as an increased likelihood of contact with the justice system (Erickson, 2012; Noltemeyer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Black and Native American youth in particular are also more likely than their White peers to be identified to receive special education services for emotional disturbance (Bal et al, 2019; Donovan & Cross, 2002) and placed in more restrictive special education settings (Skiba et al, 2006). Exclusionary discipline and restrictive special education placements is associated with decreased academic achievement (Morris & Perry, 2016) and rates of school completion (Marchbanks & Blake, 2018; Oelrich, 2012), as well as an increased likelihood of contact with the justice system (Erickson, 2012; Noltemeyer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, statistics in the United Kingdom provide clear evidence that BIPOC are more subjected to the police's "stop and search" actions (Ministry of Justice, 2018). While the relationships between social contexts, justice referrals, trends in incarceration, and racial and ethnic disparities are complex, empirical evidence supports the assertion that systemic discrimination directly contributes to the disproportionate disciplinary action against and incarceration of BIPOC (Marchbanks et al, 2018). Our field can contribute by working to improve correctional education (Davis et al, 2014).…”
mentioning
confidence: 90%
“…While it is well established that disproportionate school discipline results in increased implementation of ineffective zero-tolerance policies and potentially greater risk for contact with the juvenile justice system what is less well known are the causes of these issues (American Psychological Association Zero Tolerance Task Force, 2008; Marchbanks et al, 2018). Sources of this behavioral disproportionality vary; however, there are specific explanations in the research literature that have been suggested.…”
Section: Reasons For the Disproportionate Disciplining Of Black Childrenmentioning
confidence: 99%